China Attitude Towards the 1971 Events of Eastern Pakistan and the Indian Intrusion - Talib, Khaula (Journal of College of Education, 2019)
The attitude of the Social Republic of China towards the 1971 events in Eastern Pakistan is considered as a key phenomenon in the international relations and an attractive event in the Chinese foreign policy at that time. Despite the ideological differences between China and Pakistan and the connection of the latter with western allies, its relationship with the Republic of China was characterized by harmony. Therefore, Pakistan got full and strong diplomatic support from China during its disagreement with India that supported the separatists in Eastern Pakistan. Accordingly, the study of China’s attitude within the regional developments in Asia offers the historians and the politicians valuable lessons. It opens visions for everyone to trace the reasons and factors that influenced the Chinese foreign decision making as well as its policy on the regional and international aspects by presenting academic and scientific material for the researcher and the political decision maker in Iraq. The current study is an attempt to shed light on one of the most remarkable aspects of the separation of Eastern Pakistan, that is the role of Chinese diplomacy, its movements, vision, and reaction towards this event from the beginning of the crisis till the end as well as its significant consequences. The study will deal with this attitude through the most important speeches of the Chinese government and through the declarations of the Chinese officials as well as the positions of China in one of the most important international institutions which is the United Nations where international parties tried to discuss a[i]nd solve the crisis of Eastern Pakistan, each from a different perspective.